2020
DOI: 10.1155/2020/8867744
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Management of the Hydatid Cyst of the Liver: A Study from a Tertiary Care Center in Nepal

Abstract: A hydatid cyst of the liver is a significant yet neglected public health problem in Nepal. The present study was carried out to evaluate the demographic characteristics, clinical presentations, and management of the patients of the hydatid cyst of the liver in the setting of a developing country. It was a retrospective, descriptive analysis of 53 patients admitted in the department of surgery with the diagnosis of hydatid cyst of the liver based on clinical manifestations, imaging studies, or serology between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
1
15
1
1
Order By: Relevance
“…The liver function markers including, AST and ALT which shown in the current study are comparable to data that obtained previously in the liver fibrosis cases (13). In clinical study of cystic echinococcosis, biochemical analysis of 49 individuals showed an increase in the serum level of AST, ALT and ALP in 26.4%, 24.5% and 35.8% of the cases, respectively (14). The serum level of AST and ALT can be considered as biochemical markers of liver function, where an increase of their levels refers to damage occurring in the liver cells (15,16).…”
Section: Discussionsupporting
confidence: 90%
“…The liver function markers including, AST and ALT which shown in the current study are comparable to data that obtained previously in the liver fibrosis cases (13). In clinical study of cystic echinococcosis, biochemical analysis of 49 individuals showed an increase in the serum level of AST, ALT and ALP in 26.4%, 24.5% and 35.8% of the cases, respectively (14). The serum level of AST and ALT can be considered as biochemical markers of liver function, where an increase of their levels refers to damage occurring in the liver cells (15,16).…”
Section: Discussionsupporting
confidence: 90%
“…4 It usually remains asymptomatic for many years. 5 Symptoms and signs of hydatid cyst disease depend on the involved organ, the site, and the secondary spread. A palpable mass is the most common clinical finding.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with the findings of several researches such as study done by Fallah et al 2019 12 . Including research into Joshi et al 2020 and Al-Ani et al 2020 as well as other studies 6,10 . The liver was the location of damage in 59.45 % of cases, followed by the liver and lung in 36.03 % of cases, and the lung in 4.5 % of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical and epidemiological symptoms of hydatid cyst infection vary depending on the degree of infection, size, and location of hydatid cyst development 5 . Infection of humans with this illness has been documented in several parts of Iraq 6 . Hydatid cyst illness is extremely important; it affects vital organs in humans, particularly the liver and lungs, and it causes considerable economic losses in animals 7 .…”
mentioning
confidence: 99%